Perancangan Telescopstick Menggunakan Quality Function Deployment (QFD) - Deri Teguh Santoso; Jojo Sumarjo; Ratna Dewi Anjani (Universitas Bunda Mulia, 2017)
As the development of science is always accompanied by high-technology applications, innovation is needed to support the implementation of a technology. Almost all human activities are currently assisted by tools. Most of the families in Indonesia has a TV antenna. However, There are difficulties in the installation of antenna stick. Therefore, designing a tool in the form of a stick that can be elongated/shortened automatically is necessary for ease of use. The tool is called